Relação entre comunicação social, desempenho nas atividades de vida diária e processamento sensorial em pré-escolares com Transtorno do Espectro do Autismo (TEA) - Karina Ferreira de Oliveira (2021)
Introduction: Autism Spectrum Disorder (ASD) is characterized by impairments in reciprocal social communication, social interaction and/or repetitive behaviors and restricted interests, in addition to frequent hypo-reactivity or hyper-reactivity to sensory stimuli. The way a child communicates socially and responds to sensory stimuli can influence the performance in activities of daily living (ADL). Objective: To describe aspects of the diagnosis and perception of caregivers about the characteristics of preschoolers with ASD and investigate the relationship between social communication, sensory processing and ADL performance in preschoolers with ASD. Method: Cross-sectional descriptive study, based on clinical interview with the parents of 60 children, 46 boys and 14 girls, distributed in groups of 20 children (3, 4 and 5 years and 11 months), diagnosed with ASD by a pediatric neurologist. The level of social communication was classified by the Autism Classification System of Functioning: Social Communication (ACSF:SC). Performance on ADL and sensory processing were evaluated, respectively, by the Pediatric Assessment of Disability Inventory - Computer Adaptive Test (PEDI-CAT) and Sensory Profile (SP-2). To characterize the participants, a demographic questionnaire was used. Data were collected through face-to-face or online interviews with parents. Results: Most children (45%) had early diagnosis of ASD, with a mean age of 28.95 (±9.77) months, signaled by changes in communication, interaction and behavior. Affectionate behavior was highlighted as a strong point (33.3% of the children) by the parents and the greatest difficulties reported were related to behavior (36.6%), communication (36.6%) and performance in ADL (21.6%), which were also areas in which parents would like to see changes. There were significant (Spearman) correlations (r=0.37 to 0.65, p>0.05) between social communication (performance and ability) and the PEDI-CAT domains (T-Score), except Mobility. There was no correlation between social communication and the SP-2. In the regression analysis age, ACSF:SC Performance and male gender significantly influenced the PEDI-CAT-AVD score (p<0.001; R2= 0.31). Conclusion: Parents observe early signs of ASD that should be valued by health care professionals. Behavior management, communication and independence in ADL are relevant issues for the care of children with ASD. Social Communication had an impact on ADL, but sensory processing was not relevant. Strategies to promote ADL performance should address social communication.